FAMOUS PEOPLE OF GREAT BRITAIN IN ART - Qosimova Muslimaxon; Abdurakhmanov Turakhon Saydullayevich (TADQIQOTLAR, 2025)
Annotation:This article provides an in-depth analysis of some of the most influential British artists who have shaped the world of art. It explores their artistic styles, notable works, and contributions to movements such as Romanticism, Modernism, and Pop Art. The article also examines the historical and cultural impact of these artists, their influence on subsequent generations, and their contributions to global artistic traditions.